Controls on groundwater selenium, arsenic and base metals in groundwater around a selenium-bearing volcanogenic massive sulfide deposit: constraints from stable isotopes, trace elements and redox controls. Issue 2 (2022) - Leybourne, Matthew I.; Layton-Matthews, Daniel; Peter, Jan M.; Kidder, James A.
No abstract available